Diblock copolymer pattern protection by silver cluster reinforcement - Bulut, Yusuf; Sochor, Benedikt; Harder, Constantin; Reck, Kristian; Drewes, Jonas; Xu, Zhuijun; Jiang, Xiongzhuo; Meinhardt, Alexander; Jeromin, Arno; Kohantorabi, Mona; Noei, Heshmat; Keller, Thomas F; et al. (Nanoscale, 2023)
Pattern fabrication by self-assembly of diblock copolymers is of significant interest due to the simplicity in fabricating complex structures. In particular, polystyrene- block -poly-4-vinylpyridine (PS- b -P4VP) is a fascinating base material as it forms an ordered micellar structure on silicon surfaces. In this work, silver (Ag) is applied using direct current magnetron sputter deposition and high-power impulse magnetron sputter deposition on an ordered micellar PS- b -P4VP layer. The fabricated hybrid materials are structurally analyzed by field emission scanning electron microscopy, atomic force microscopy, and grazing incidence small angle X-ray scattering. When applying simple aqueous posttreatment, the pattern is stable and reinforced by Ag clusters, making micellar PS- b -P4VP ordered layers ideal candidates for lithography. The pristine micellar pattern of the diblock copolymer PS- b -P4VP degrades upon drying of a water droplet, which can be stabilized and inhibited upon deposition of silver clusters.